ANALISIS RETURN ON ASSET, RETURN ON INVESTMENT, DAN EARNING PER SHARE TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR BEI - Zahra, Nurjanatul; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2021)
This research was conducted to examine the effect of ROA, ROI and EPS on Stock Prices in Manufacturing Companies on the Indonesia Stock Exchange. This study tested several manufacturing companies in the consumption industry sector that displayed their financial reports for the period 2015 to 2019. The results of the normality test show that the research data is normally distributed. Based on the multicolonierita test, autocorrelation test, and heteroscedasticity test, there were no deviations from the classical assumptions. The result of ROA research partially does not have a significant effect on stock prices with a significant value of 0.00, which means that the value is less than 0.005. ROI variable has a significant effect on stock prices with a significant value of 0.759 greater than 0.05. And the EPS variable has a significant effect on stock prices with a significant value of 0.348 greater than 0.05. ROA, ROI, and EPS variables simultaneously have a significant effect on stock prices with a significant value of 0.00. With a determination coefficient of 39,0 percent, which means that the variables ROA, ROI, EPS affect the stock price by 39,0 percent and the rest is influenced by other variables not included in this study.